Collaboration multiprofessionnelle dans un contexte d'enseignement spécialisé : activité déployée pour la conception, la mise en œuvre et la régulation d'un projet d'élève - Roland Emery; Greta Pelgrims (Nantes Université, 2015)
Based on a situated action approach, our research aims to describe the multiprofessional activity unfolded by the members of a special school's team to design an Individualized Education Program (IEP). The study shows the flow of individual and collective activity of 8 professionals during 6 month. It examines the zone of complementarities, convergences and divergences in the meaning granted to this activity by the various professional. The results show the importance of the ongoing links during IEP designing between many informal interactions and formal team meetings. These informal interactions occur during the period of observation and decision for IEP both outside with professional partners of the special education school, and inside between team members. In articulation, formal team meetings are devoted to exchange information collected in the informal interactions in order to decide and formalize the IEP. Our findings show the gap between the prescriptive work how to design an IEP and actual activity.